Dramaturgy Of Street Performers In Jakarta (A Social Construction Study on The Phenomenon Of Metropolitan Life) - Sukma, Agus Hitopa; Pranawukir, Iswahyu; Misnan, Misnan; Bachtiar, Alfan; Hiswanti, Hiswanti; Alamsyah, Alamsyah (LPPM Universitas PGRI Sumatera Barat, 2024)
Life in Jakarta reflects complex social phenomenon, especially related to social inequality striking. This research aims to analyze the dynamics of interaction Street buskers as social